2020
DOI: 10.1111/andr.12746
|View full text |Cite
|
Sign up to set email alerts
|

FSH treatment of male idiopathic infertility: Time for a paradigm change

Abstract: Follicle-stimulating hormone (FSH) has been used in inconclusive clinical trials for male idiopathic infertility in the past. FSH is sometimes prescribed empirically for male idiopathic infertility, showing some improvement in sperm parameters in about half of the patients. In this opinion article, we briefly analyze the pathophysiological evidences in favor of a more aggressive approach in planning future studies on pharmacological FSH use in male infertility, in analogy with the FSH use for multiple follicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 92 publications
3
47
0
Order By: Relevance
“…A recent Italian nation-wide survey evaluated the idiopathic male infertility management, detecting an FSH prescription rate of 55% [5]. Although this study was not designed to detect FSH efficacy in male infertility, it showed a slight increase in semen parameters in about half of the treated men, confirming the need for properly designed larger clinical trials in this setting [5,52].…”
Section: Therapeutic Options To Improve Sperm Productionmentioning
confidence: 88%
See 2 more Smart Citations
“…A recent Italian nation-wide survey evaluated the idiopathic male infertility management, detecting an FSH prescription rate of 55% [5]. Although this study was not designed to detect FSH efficacy in male infertility, it showed a slight increase in semen parameters in about half of the treated men, confirming the need for properly designed larger clinical trials in this setting [5,52].…”
Section: Therapeutic Options To Improve Sperm Productionmentioning
confidence: 88%
“…However, qualitatively and quantitatively adequate spermatogenesis requires FSH action and high intratesticular testosterone levels, acting in additive and synergistic ways [51]. These data provide new perspectives in the therapeutic approaches to male infertility, similar to what is currently done in women undergoing ART [52].…”
Section: Physiological Control Of Spermatogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this approach has the limitation of relatively high costs and off-label usage [114], so that only limited clinical data are available [112,113]. To date, seventeen clinical trials evaluated FSH use in idiopathic infertile men and were listed in an opinion article [115], obtaining different results. These data were recently meta-analyzed and suggested that the use of FSH may increase overall pregnancy rates, which, however, was never considered as the primary end point in the original studies [116,117].…”
Section: Fsh Use In Idiopathic Infertility: State-of-the-artmentioning
confidence: 99%
“…A semen sample will be taken from 50 infertile men that referred to highly specialized infertility treatment center of ACECR (academic center of education, culture, and research, Qom Branch). The inclusion criteria were the low level of FSH (<1.7 mIU/mL), aged 25-45 years, history of infertility for at least 2 years, sperm concentration <15×106 (oligozoospermia) according to 2010 World Health Organization criteria [13,14]. Under the supervision of a urologist, all enrolled patients received subcutaneous recombinant FSH (Gonal-f) treatment, 75 IU every other day, starting from Visit 1, for three months, three times a week.…”
Section: Methodsmentioning
confidence: 99%